Video Edukasi Kontrasepsi Islami Dalam Meningkatkan Pengetahuan PUS Tentang Metode Kontrasepsi Islami Di PMB Nenden Kopo Bandung - Mochamad Salman Hasbyalloh; Niknik Nursifa; Hana Nurhanifah Budiadi (Jurnal Kesehatan Rajawali, 2023)
Information on Islamic contraception in ripe-age couples is still extremely low. The number of couples of childbearing age who are unaware of the Islamic Family Planning (KB) method is influenced by a number of factors, including education. One technique that can give information to fruitful age couples is utilizing the Varying media Strategy Wellbeing. This study was conducted at the Midwifery Clinic "Bidan Nenden" to ascertain the impact of audiovisual health education on knowledge of Islamic contraception among couples of reproductive age. The examination strategy utilizes Trial One Gathering Pretest-Posttest Plan Without Control. The proposed sampling method was used to select 45 participants for the study's sample. The findings demonstrated that prior to receiving the Audiovisual Method Health Education, respondents with less knowledge had the highest level of knowledge—21 (46.7%)—while those who received it had the highest level of knowledge—23 (51.1%). Based on the results of the paired t-test, P value of (0.000) (0.05) was found to be the effect of audiovisual health education on knowledge of Islamic contraception among couples of reproductive age, Ho is rejected. Conclusion: there is an impact of well-being instruction about contraception as indicated by Islam on the information on Discharge about contraception as per Islam. The idea is the decision of the Birthing assistance Facility 'Bidan Nenden' and well-being authorities can further develop medical care administrations in aiding Rich Age Couples by giving great Varying media Strategy Wellbeing Training.